Single-port laparoscopic sacrospinous ligament suspension via the natural vaginal cavity (SvNOTES) for pelvic prolapse: The first feasibility study - Lyu, Yuanyuan; Ding, Huafeng; Ding, Jin; Luo, Yonghong; Guan, Xiaoming; Ni, Guantai (Frontiers in Surgery, 2022)
Objective This study aims to investigate the feasibility and short-term efficacy of single-port laparoscopic-assisted transvaginal natural cavity endoscopic sacrospinous ligament suspensions (SvNOTES). Methods A total of 30 patients diagnosed with anterior or/and middle pelvic organ prolapse Stages III and IV underwent natural vaginal cavity (SvNOTES), and 30 patients who underwent conventional sacrospinous ligament (SSLF) were used as a control group. The operation time, blood loss, postoperative POP-Q score, length of hospital stay, and complications were compared between the two groups. Results The operation time for SvNOTE was (60 ± 13) min, which was longer than (30 ± 15) min for SSLF (P = 0.04). However, the bleeding amount in SvNOTE was 29.44 ± 2.56, significantly lower than that in the SSLF group (80 ± 10; P = 0.02), and the postoperative hospital stay in the SvNOTE group was (4 ± 2) days, longer than (3 ± 1) days in SSLF (P = 0.02). However, there were no intraoperative complications in the SvNOTE group, whereas one ureteral injury occurred in the SSLF group; in addition, the postoperative POP-Q score was significantly better in the SvNOTE group than that in the SSLF group with increasing time (P < 0.001). Conclusion Compared with SSLF, single-port laparoscopic sacrospinous ligament suspension via the natural vaginal cavity is visualized, greatly improving the success rate of sacrospinous ligament fixation, with less blood loss and fewer complications, arguably a safer and minimally invasive surgical approach.